ХАЛЫҚТЫҢ КӨРКЕМ МИЙРАСЫН БАҲАЛАЎДЫҢ БАЗЫ БИР МӘСЕЛЕЛЕРИ («Шәрияр» дәстаны мысалында) - Кеңесбаева, Ш. (SCIENCE and SOCIETY, 2016)
The article is devoted to the study of the genesis, genre and form peculiarities, national character of the epos «Shariyar», that is an epic work of Karakalpak folklore. The subjective points of view on these issues have been discussed. In conclusion, the author of the article claims to value objectively the national heritage, taking into account the ideas of national independence on the example of the epos «Shariyar».
Keywords: creative heritage; epos «Shariyar»; genesis; peculiarities of the genre; historical genesis of typology; typology and national peculiarities